Factors Affecting Maternal Health Care Delivery in the Komenda Edina Eguafo Abrem Municipality of the Central Region - Eshun, P (University of Ghana)
This study was carried out to investigate factors affecting maternal health care delivery in the Komenda Edina Eguafo Abbrem Municipality. Qualitative and quantitative methods were used to elicit information for the study. For quantitative method, simple random and snow ball sampling procedures were used to sample 150 respondents for the survey. In-depth interviews and focus group discussions were employed to solicit information for the qualitative data. The findings of the study showed that, there was an imbalance in the midwife-patient ratio causing delays in response time to treatment and subsequently affecting the quality of services provided. Also, poor road networks, distance and cost, increase travel time to health facilities, a move compelling pregnant women to resort to traditional birth attendants. The study also found that, majority of the respondents associated their inability to access health care to their limited income levels. This was attributed to the hidden charges associated with antenatal care and delivery despite the use of the National Health Insurance card. Dietary superstitions were found to be the main socio-cultural practice among respondents. The study concluded that inadequate midwives, deplorable state of roads, dietary superstitions associated with pregnancy and financial burdens are factors deterring pregnant women from accessing maternal health care services and hence the slight decline in ANC attendance rate. It was therefore recommended that staff strength, especially midwives need to be improved to ensure efficiency. Roads linking communities to health facilities as well as referral and communication systems need to be improved to ease referrals and also make access to health facilities easier for those in hard-to-reach areas. Maternal health education also needs to be intensified to eradicate cultural practices that affect maternal health.
Keywords: FACTORS; AFFECTING; MATERNAL HEALTH; DELIVERY; CARE; KOMENDA EDINA EGUAFO ABREM MUNICIPALITY; CENTRAL REGION